徘徊による行方不明を経験した家族の苦闘 - 横瀬 利枝子 (生命倫理, 2015)
In this study, surveys in the form of interviews were conducted with eight caregivers that have experienced wandering of people with early onset dementia. Instances of extreme situations in providing care to wandering patients, situations where patients had gone missing unexpectedly, assistance, patient and caregiver struggles, and ethical problems were examined. Also, measures taken mainly by the community such as the Associations of Families were also examined. As a result, it was discovered that caregivers experienced missing patients due to slight moments of inattentiveness while providing strenuous 24-hour nursing care. Caregivers had repeatedly made requests to the police to conduct searches, encountered sleepless nights, and faced economic hardship. All of the caregivers had experienced instances where they had expected to bid their final farewell to the patient. In many cases, patients gradually forget about their family and hardship continues for both patient and family members. Although awareness has not spread for people with early onset dementia, no support system has been established, and many of the caregivers involved are exhausted and beyond their ability to provide care, each of the subjects willingly spoke about their thoughts on providing care. Communities have initiated their efforts to provide assistance. 本研究では、若年性認知症者の配偶者の俳回による行方不明を経験した8名の介護者に、聞き取り調査をおこない、俳回を伴う介護の壮絶な状況、予期せぬ行方不明当時の状況、支援について、本人および介護者の苦闘と倫理的課題を検討するとともに、家族の会などがおこなっている市民主体の共助の取り組みについても検討した。その結果、対象者の誰もが苛酷な24時間介護を続ける中、一瞬の気の緩みによって、配偶者の行方不明を経験していた。警察への捜索願を繰り返しながら、眠れぬ日々の中で、経済的困窮が迫りくる。対象者の誰もが、今生の別れの予感を経験していた。家族が次第に忘れられる事例も多く、患者、家族双方にとって苦闘の日々が続く。しかし、若年性認知症への理解が進まず支援体制が整わない中で、対象者の多くが疲弊し、介護の限界を超えていたにもかかわらず、誰もが自らの介護への内省を語った。市民共助の取り組みも始まっている。